Dual polarization-enabled ultrafast bulk photovoltaic response in van der Waals heterostructures - Zeng, Zhouxiaosong; Tian, Zhiqiang; Wang, Yufan; Ge, Cuihuan; Strauß, Fabian; Braun, Kai; Michel, Patrick; Huang, Lanyu; Liu, Guixian; Li, Dong; Scheele, Marcus; Chen, Mingxing; et al. (Nature communications, 2024)
The bulk photovoltaic effect (BPVE) originating from spontaneous charge polarizations can reach high conversion efficiency exceeding the Shockley-Queisser limit. Emerging van der Waals (vdW) heterostructures provide the ideal platform for BPVE due to interfacial interactions naturally breaking the crystal symmetries of the individual constituents and thus inducing charge polarizations. Here, we show an approach to obtain ultrafast BPVE by taking advantage of dual interfacial polarizations in vdW heterostructures. While the in-plane polarization gives rise to the BPVE in the overlayer, the charge carrier transfer assisted by the out-of-plane polarization further accelerates the interlayer electronic transport and enhances the BPVE. We illustrate the concept in MoS 2 /black phosphorus heterostructures, where the experimentally observed intrinsic BPVE response time achieves 26 ps, orders of magnitude faster than that of conventional non-centrosymmetric materials. Moreover, the heterostructure device possesses an extrinsic response time of approximately 2.2 ns and a bulk photovoltaic coefficient of 0.6 V −1 , which is among the highest values for vdW BPV devices reported so far. Our study thus points to an effective way of designing ultrafast BPVE for high-speed photodetection. The bulk photovoltaic effect (BPVE) has potential for the realization of high conversion efficiency optoelectronic devices. Here, the authors show that combined in-plane and out-of-plane charge polarizations in MoS 2 /black phosphorus heterostructures can enhance the BPVE and reduce the extrinsic response times down to 2.2 ns.